Lithium, beryllium, boron as indicators of matter evolution - Klochkova, V. G.; Panchuk, V. E. (Одеські астрономічні публікації, 2017)
A historic review of the 293 papers, contained as the results of observations and the  description of the processes  of production and destruction of the light elements Li, Be, B are presented.